Antibacterial potential with evidential molecular docking analysis and catalytic performance of multiple phases AgBr and PVP doped BaO nanorods - Ikram, Muhammad; Shahzadi, Iram; Haider, Ali; Moeen, Sawaira; Khan, Khadija; Ul-Hamid, Anwar; Mateen, Zernab; Asiri, Mohammed; Ullah, Hameed [UNESP] (Elsevier, 2025)
This study acknowledges the imperative requirement for effective and sustainable approaches to deal with organic pollutants and waterborne microbial contamination. This work presents the synthesis of different concentrations (2 and 4 %) of silver bromide (AgBr) with a fixed quantity of polyvinylpyrrolidone (PVP) doped into barium oxide (BaO) nanorods (NRs) via co-precipitation method. To improve the decolorization of rhodamine B (RhB) and antimicrobial activity against Staphylococcus aureus (S. aureus) with molecular docking analysis by controlling the size of NRs and reducing the recombination rate was the focus of this research. The possible ways of improving the BaO morphology, structure, and optical properties have been performed using developed characterization techniques. XRD analysis revealed the tetragonal structure of synthesized NRs, and an increase in crystallinity was observed upon doping. Electronic spectra revealed doping of BaO with PVP and AgBr narrowed the bandgap energy (Eg) from 3.81 to 2.86 eV AgBr/PVP-doped BaO NRs showed a remarkable catalytic efficacy of over 86.63 % for dye degradation in neutral pH, signifying its application in various environments. Additionally, doped NRs exhibit excellent microbicidal effectiveness against S. aureus, with an inhibition zone of 12.45 mm. The docking studies were executed to inquire prohibitive ramifications of PVP-BaO and AgBr/PVP-BaO NRs on DNA gyrase enzymes in S. aureus, in conjunction with their microbicidal efficacy.